MediTrack Healthcare System - Gade Neha; Wagaskar Aarti; Gursali Apurva; Takale Rupali; Prof. Kanade R. S. (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Meditrack healthcare system presented addresses the critical need for a scalable, secure, and user-centric platform for handling electronic medical records across multiple healthcare institutions. Built upon a modern MERN (MongoDB, Express.js, React.js) stack with Next.js for server-side rendering and performance optimization, our system streamlines the processes of patient registration, doctor-patient communication, appointment scheduling, and permissioned sharing of sensitive medical data. Emphasis is placed on robust role-based access control (RBAC) mechanisms to ensure data privacy and regulatory compliance, while leveraging JSON Web Tokens (JWT) and HTTPS for authentication and transport security. The system’s modular microservices architecture enables easy customization and integration with existing hospital information systems, facilitating rapid deployment and minimal disruption to clinical workflows.
Keywords: Electronic Medical Records (EMR); Role-Based Access Control (RBAC); MERN Stack; Healthcare Data Security; Microservices Architecture